Twenty-first century drama the first decade - Courtney, Angela 1967- (Gale virtual reference library., 2012)
Provides first or unique coverage of both domestic and international works of drama from the first decade of the 21st century, featuring in-depth information on around 175 plays and musicals first produced between the years 2000 and 2009.